TOTAL FENOLIK, FLAVONOID, DAN AKTIVITAS ANTIOKSIDAN PRODUK TEH HIJAU DAN TEH HITAM TANAMAN BANGUN-BANGUN (Coleus amboinicus) DENGAN PERLAKUAN ETT REMPAH-REMPAH - Restauli Br Siburian; Christine Jose; Ganis Fia Kartika (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Coleus amboinicus is a plant with good antioxidant content . Antioxidants are very important in preventing various diseases caused by free radicals. The high antioxidant content of plant C. amboinicus potentially used as raw material for making herbal tea products, such as green tea and black tea. The objective of this research was to analyze the total phenolics, flavonoids and antioxidant activity of green tea and black tea prepared from C. amboinicus plants with two different treatment, fermented plant extract (FPE) spice and control (water). The results showed that the total phenolic and flavonoid content of each treatment was different. The total phenolic content of control treatment and FPE spice green tea and black tea products were 16,660 ± 0.251 mg AGE/g DW; 10.510 ± 0.737 mg AGE/g DW and 14,219 ± 0,198 mg AGE/g DW; 8.062 ± 0.334 mg AGE / g DW. Were the total flavonoids treatment control and FPE spice green tea and black tea is 3.522 ± 0.077 mg CTE/g DW; 2.141 ± 0.104 mg CTE/g DW and 2.278 ± 0.057 mg CTE/g DW; 2.077 ± 0.044 mg CTE/g DW. The content of antioxidant activity by FTC method is highest shown in the control treatme nt compared with ETT RR good green tea products and black tea. It can be concluded that green tea product of C. amboinicus is better source of flavonoids, phenolics and antioxidant activity compared with the black tea product.